2004
DOI: 10.1111/j.1365-2621.2004.tb13364.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behavior of Refrigerated Frozen Low‐moisture Mozzarella Cheese

Abstract: The effect of freezing low-moisture Mozzarella before ripening on cheese microstructure and its relationship with caseins degradation and viscoelastic properties were analyzed, and results were compared with refrigerated control samples. Soluble and nonprotein nitrogen contents increased with ripening time although more rapidly in the samples that were frozen before ripening. Scanning electron microscopy (SEM) showed that freezing modified cheese microstructure due to ice formation; ice crystals weakened the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
2
39
0
1
Order By: Relevance
“…The negative correlation indicates that when MI increased the rheological parameter a decreased. This observation reaffirms the importance of proteins in cheese texture that was previously published by other authors [2,5,24]. The proteolysis of LFSC produced an increase in the pH 4.6-soluble nitrogen compounds that cannot contribute to the protein network.…”
Section: Kinetic Analysis Of Rheological Parameterssupporting
confidence: 77%
See 2 more Smart Citations
“…The negative correlation indicates that when MI increased the rheological parameter a decreased. This observation reaffirms the importance of proteins in cheese texture that was previously published by other authors [2,5,24]. The proteolysis of LFSC produced an increase in the pH 4.6-soluble nitrogen compounds that cannot contribute to the protein network.…”
Section: Kinetic Analysis Of Rheological Parameterssupporting
confidence: 77%
“…According to Gravier et al [5], tan δ can be used to indicate the strong relationship between the viscous behavior and the degree of casein hydrolysis. Values of tan δ of LFSC were between 0.3 and 0.55, indicating that elastic properties predominate at any ripening time.…”
Section: Mechanical Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were fixed with Carnoy fluid at 4°C for 24 hr and dehydrated using gradually increasing concentrations of ethyl alcohol (Graiver et al, 2004). The fixed and dehydrated samples were mounted on aluminum stubs using a double sided tape and then coated with a layer of gold (40-50 nm), allowing for surface and cross-section visualization.…”
Section: Microstructurementioning
confidence: 99%
“…Particularly, the large differences between G' and G" were observed for OBC, which suggested that the material should be classified rheologically as elastic gels (Lee & Inglett 2006;Lai & Cheng, 2004). It is known that if G' > G", the materials exhibited a viscoelastic solids behavior and the deformation on the linear range will be essentially elastic or recoverable (Gravier et al, 2004). The highest storage G' and loss G" moduli values were observed for OBC among all samples, indicating OBC had the greatest viscoelastic properties, which were contributed by the network forming with strong amylose and amylopectin interactions of OBC.…”
Section: Rheological Propertiesmentioning
confidence: 99%